Will MOOCs transform learning and teaching in higher education? Engagement and course retention in online learning provision - De Freitas, S.; Morgan, J.; Gibson, David (Wiley-Blackwell, 2015)
Massive open online courses (MOOCs) have been the subject of much polarised debate around their potential to transform higher education in terms of opening access. Although MOOCs have been attracting large learner cohorts, concerns have emerged from the early evidence base centring upon issues of quality in learning and teaching provision, and there is clear evidence that impressive headline figures on MOOC enrolments often contrast with extremely low course completion rates. To address these concerns of quality, low retention and the need for engagement, this paper provides a review and case study of MOOC provision. The review considers the current position of MOOCs as a change agent for higher education provision, and the case study considers lessons learnt from an Astronomy MOOC which uses the Open2Study platform. This paper asks about new engagement strategies needed for face-to-face and online learners, and explores how course retention can be improved in online provision.